EVALUASI PENGGUNAAN BUKU KESEHATAN IBU ANAK, KARTU IBU, REGISTER ANC DI PUSKESMAS - Herinawati Herinawati; Sri Yun Utama; Atika Fadhilah Danaz Nst; Nuraida Nuraida; Iksaruddin Iksaruddin (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: Maternal and child health services including immunization, disease records and child development problems must be recorded completely and correctly. The MCH Handbook is useful for monitoring maternal and child health. The use of maternal and child health services is still constrained by the lack of synchronization between the MCH books that the mother will bring home, and the mother's card that is archived at the puskesmas so that there are several points of information in the MCH book that are not on the mother's card so that it will be difficult to find data and make a report. Methods: This study used a PICOS review literature study method with 7 articles using the PRISMA approach. The objective of this study was to determine the evaluation of the use of the MCH booklet, mother card, and ANC register at the health center. Using the keywords "MCH Handbook", "Mother's card", "ANC register" and "evaluation" from quantitative or qualitative studies. Complete articles published in 2010-2020, in Indonesian or English, review, comparative, or cross-sectional research types. The articles are then evaluated using critical analysis. Results: The recording of mother cards that was filled in but was incomplete was mostly in the maternal examination column, namely 64% and examination of babies by 63%. The lack of use of the mother card as a documentation tool was 82.1% of respondents. The column on the mother card with the most blanks is in program integration (PMTCT, Malaria, TB) as much as 75%. The results of the MCH book recording function were less than 44%. Conclusion: The health system needs to be adjusted to introduce the use of the handbook. Policymakers should have a clear vision and goals from the MCH handbook for strengthening health care systems.